2012
DOI: 10.1128/jcm.00763-12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Streptococcus pneumoniae in Respiratory Samples from Patients with Tracheostomy in a Long-Term-Care Facility

Abstract: We aimed to study the prevalence of Streptococcus pneumoniae in respiratory samples from institutionalized patients with chronic tracheostomy. A total of 264 pairs of nasopharyngeal and endotracheal cultures were collected. There was no difference in the proportion of positive cultures between children (21%) and adults (18%). However, the proportion of positive endotracheal cultures was higher than that of nasopharyngeal cultures in adults (18% versus 3%, respectively; P < 0.001) but not in children (17% in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…Finally, it should be emphasised that only symptomatic patients were receiving antibiotics during rehabilitation (data not shown) and this may possibly lead to more bacterial colonisations. Interestingly, S. pneumoniae was detected only twice in our cohort, at variance with other studies that reported higher prevalence in long-term tracheostomised patients [30]. The relative prevalence we found among species was in fact very similar to the one described in a recent review on nosocomial pneumonia [2]; possible explanations of discrepancies in the reported prevalence of S. pneumoniae may comprise, but are not limited to, different geographical locations (involving different provenance hospitals and environments) and treatment habits, both before and during rehabilitation.…”
Section: Discussioncontrasting
confidence: 84%
“…Finally, it should be emphasised that only symptomatic patients were receiving antibiotics during rehabilitation (data not shown) and this may possibly lead to more bacterial colonisations. Interestingly, S. pneumoniae was detected only twice in our cohort, at variance with other studies that reported higher prevalence in long-term tracheostomised patients [30]. The relative prevalence we found among species was in fact very similar to the one described in a recent review on nosocomial pneumonia [2]; possible explanations of discrepancies in the reported prevalence of S. pneumoniae may comprise, but are not limited to, different geographical locations (involving different provenance hospitals and environments) and treatment habits, both before and during rehabilitation.…”
Section: Discussioncontrasting
confidence: 84%
“…The study by Adler et al . 2012 identified the serotype of isolates; however, they did not differentiate the isolates from adult and pediatric patients [ 4 ]. The serotypes of the 45 isolates from the trachea or trachea and nasopharynx were 23F, 19F, 17F, 15A, 6A and non-typeable.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of colonization are higher in children than adults and certain groups of patients could be at increased risk of developing pneumococcal infection [ 1 3 ]. Patients with tracheostomies have pneumococcal colonization of their lower respiratory tract; however, little is known about the strains colonizing these patients [ 4 , 5 ]. A study published in 1979 examined pneumococcal colonization of 27 children (mean age of 8.5 years) biweekly over a one year period [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-Loss of natural protection by oral and nasal fence allowing direct contamination of microorganisms in the trachea and bronchi. There are very few correlations in microorganisms between the upper aerodigestive tract and the tracheobronchial tract [14][15][16].…”
Section: Recommendationsmentioning
confidence: 99%